Determinants of quality of the financial statements of Gunung Kidul Regency Government - Marfuah Marfuah; Eliza Nur Istiqomah; Chivalrind Ghanevi Ayuntari; Priyono Puji Prasetyo (Journal of Contemporary Accounting, 2023)
This study aims to determine the effects of human resource competence, internal control system, application of government accounting standards, utilization of information technology, and regional financial supervision on the quality of local government financial reports of Gunung Kidul Regency. The population of this study is the Regional Work Units in Gunung Kidul Regency. The sampling method used was purposive sampling where 86 respondents were selected as the research samples. The results of this study indicate that the competence of human resources, internal control system, application of government accounting standards, use of information technology, and regional financial control have proven to have significant and positive effects on the quality of local government financial reports of Gunung Kidul Regency. This result contributes to improving the quality of financial reports of Gunung Kidul Regency Government by upgrading the competence of its employees in accounting and finance, establishing effective internal control system, applying the government accounting standards, maximizing the use of information technology, and performing regional financial supervision.